A study on prevalence of peste des petits ruminant (PPR) in goat at Bagmara upazilla at Rajshahi district in Bangladesh - Rahman, Md Mostafijur; Alam, Khondoker Jahengir; Alam, Md Shah; Hasan, Md Mahmudul; Moonmoon, Monalisha (Research in Agriculture Livestock and Fisheries, 2016)
A study was conducted at Bagmara upazilla under the district of Rajshahi in Bangladesh during the period of 2 month from 20 September 2015 to 14 November 2015 to determine the prevalence of PPR in goat. A total of 72 diseases cases were recorded randomly irrespective of age, sex and breed over the study period. In the present study the overall prevalence of PPR in goat was 27.78%. In black Bengal goat, the prevalence of PPR in different age group i.e. up to 6 month, 7-12 month, 13-19 month, above 19 month were 18.18%, 42.30%, 22.22% and 12.50%, respectively. Over all, female black bengal goat (46.42%) was more infected than male (12.00%). The prevalence of PPR in different age group i.e. 7-12 month, 13-19 month were 42.85% and 25.00%, respectively; and males (16.66%) and female (23.07%) of Jamunapari goat were recorder. In general, black bengal goats have the higher prevalence (30.18%) than Jamunapari goat (21.05%). The nonimmunized goat showed higher prevalence (38.77%) than immunized (4.34%) goat. All data were analyzed by using ?2 tests with P value at (P<0.05) level of significance. Res. Agric., Livest. Fish.3(2): 339-344, August 2016